Remifentanil vs. propofol controlled infusion for sedation of patients undergoing gastrointestinal endoscopic procedures: A clinical randomized controlled clinical trial (2013)
Background: Target controlled infusion (TCI) for the administration of anesthesia may provide a safe alternative for managing the discomfort of patients undergoing gastrointestinal endoscopic procedures. However, the most appropriate drug available for TCI is yet to be established. The objective of this trial was to compare remifentanil vs. propofol in TCI for sedating patients during GI endoscopy. Materials and methods: Sixty-nine patients requiring GI endoscopies were randomly distributed to receive remifentanil (n = 30) or propofol (n = 39) TCI at the effect site (e). The primary outcome was patient's satisfaction. Secondary outcomes included the gastroenterologist satisfaction, comparison of the percentage of adverse events between the two groups (occurrence of arrhythmias, major respiratory depression, bradycardia, hypotension, pain, nausea or vomiting and absence of amnesia), and the level of awareness. Retrospective registration number is NCT01746641 at Clinicaltrias.gov Results: The mean (range) of patient satisfaction with remifentanil vs propofol was 1 (1-2) and 2 (11), respectively (Chi2, p < 0.001). Pain during the procedure was found to differ between remifentanil and propofol (mean 2 vs. 1, Chi2, p = 0.042), nausea or vomiting (4 vs. 0, Chi2, p = 0.01), and absence of amnesia (29 vs. 10, Chi2, p < 0.001), respectively. No statistically significant differences were found between the two groups. Conclusion: Propofol in TCI seems to be an adequate agent for sedation of patients undergoing GI endoscopic procedures, with less adverse effects and higher patient satisfaction. Most likely, the combination of these two drugs may be synergistic and further reduce any adverse effects.